Nanotechnology in the process of precision casting of precious alloys - Rudolf, Rebeka; Majerič, Peter; Ferčec, Urban (Anali PAZU, 2022)
Precision casting is a process based on the casting and solidification of the melt on the "removed wax"1. The advantages of precision casting are high precision, smoothness of the surface and integrity of the manufactured castings, and all the features can also be used in Nanotechnology2. The so-formed castings from cobalt, chromium, titanium and silver/gold alloys have been known for years as biocompatible materials with exceptional elastic properties3, and are used in the fields of Orthopaedics and Dentistry, and in the manufacture of many medical devices4. On the other hand, highly-used nanoparticles of precious metals are today based mainly on gold. They exhibit unique physical and chemical properties, such as large reaction surfaces, good absorption and conductivity5. Since alloys based on gold or silver at the macro level exhibit distinctly different properties than gold and silver nanoparticles on a micro level, the latter are the subject of many recent researches, and, consequently, many new applications6,7,8. However, most of the research in the field of Precision Casting of precious metals does not focus on Nanotechnology, which represents a great research potential. Using Nanotechnology or improved pre-casting, we would thus acquire completely new properties of materials, useful in many areas, with the primary goals in medicine. The presentation of this approach and the categorization of these processes is, thus, the main goal of the work, in which the new alloying process and the characterization of their properties are presented, which is an important source for future research.
Keywords: precision casting; Nanotechnology; precious alloys; properties